Safety evaluation of silver-ion dressings in a porcine model of deep dermal wounds: A GLP study. (1st February 2020) - Barillo, David J.; Croutch, Claire R.; Barillo, Anthony R.; Reid, Frances; Singer, Al
Highlights: Silver ion has strong antimicrobial properties. Silver-plated nylon dressings are commonly used in burn and wound care. The safety of silver-nylon dressings has been well studied in animal models of burn injury. Prolonged use leads to increased wound levels of silver ion in the wound, along with negative levels in blood and organs. Silver-nylon dressings are also used in acute and chronic (non-burn) wounds. The safety profile for these indications is not as well defined. We tested the safety profile of silver-nylon dressings applied for 21 days over partial thickness open skin wounds in a Gottingen pig model. A control group receiving moist gauze dressings was included for comparison. Silver ion levels in all wounds were elevated after 21 days of silver-nylon dressing treatment and remained elevated after another 14 days of no treatment. Silver ion was not detected in blood, liver or kidney of any animal treated with silver-nylon or control dressings. Blood chemistry indices of kidney and liver function remained normal in all groups. Hematology indices remained normal in all groups. Abstract: Introduction: Silver ion has strong antimicrobial properties and is used in a number of wound dressings. In burn models, silver-nylon dressings produce elevated silver levels in the wound along with minimal systemic effect. We evaluated systemic toxicity in a non-burn wound model to see if a similar pattern of silver ion distribution would occur. Methods: Eight deep partial-thickness wounds each were created on the dorsum of 40 Gottingen minipigs using a Er-YAG Laser. Half were treated with a 21-day course of silver-nylon dressings (Silverlon®) and half were treated with moist gauze dressings. Wound, blood, liver and kidney silver levels, along with blood chemistry and hematology data were obtained at appropriate intervals. Results: All wounds healed well with healing enhanced by silver-nylon dressings. Silver ion was demonstrable in all wounds treated with silver-nylon at day 21 and after 14 days of no further treatment. Silver ion was not detected in blood, liver or kidney of any animal treated with silver-nylon or control dressings. Liver and kidney function remained normal in all animals. Conclusion: A 21-day application of silver-nylon dressings to a non-burn dermal wound produces no systemic or local toxicity in Gottingen minipigs.